Discursos contemporâneos sobre Montes Claros: (re) estruturação urbana e novas articulações urbano-regionais - Fernanda Silva Gomes (2007)
The transformation of Montes Claros from an Agrarian-Mercantile City to an Urban-Industrial City reflects directly on the configuration of its urban structure: the expansion of the urban tissue"; the "periphericization" of land-use and landoccupation; the proliferation of subnormal housing; the segregation within urban space; the decentralization of downtown and the emergence of new centralities.Montes Claros also changed from a Monocentric City to a Policentric City. The process of urban restructuring in Montes Claros is associated to its coming out as a City-Region and to its consolidation as a tertiary and industrial pole within the urban network of Northern Minas Gerais. The objective of this research is to discuss Montes Claross urban structure current tendencies of socio-spatial configuration and its new urban-regional articulations.